Tata Kelola Program Makan Bergizi Gratis di Kota Kupang - Trimerta Kirana Modok; Laurensius P. Sayrani; Delila A.N. Seran; I Putu Yoga B. Pradana (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The Free Nutritious Meal Program (MBG) is a national strategic initiative aimed at improving students’ nutritional status and strengthening human resource quality. However, the large budget allocation and implementation complexity require effective, transparent, and accountable governance. This study aims to analyze the governance of the MBG Program in Kupang City based on management, transparency, and accountability aspects. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. Informants were selected using purposive sampling, including representatives from the Education Office, SPPG, schools, and student beneficiaries. Data were analyzed using the Miles and Huberman interactive model and validated through source, technique, and time triangulation. The findings indicate that administratively the program implementation complies with technical guidelines; however, substantive gaps remain. Menu planning is centralized and minimally participatory, procurement and distribution mechanisms have not fully met transparency and quality control standards, student socialization is limited, and reporting as well as complaint handling systems remain internally oriented and insufficiently documented. Therefore, the governance of the MBG Program in Kupang City is still predominantly administrative in nature and requires strengthened participation, transparency, and integrated oversight systems to ensure sustainable impacts on students’ nutritional improvement.